A Cross-Sectional Study Analyzing Predictors of Perceived Stress Among Elementary School Teachers During the COVID-19 Pandemic. (April 2022) - Parthasarathy, Nivedhitha; Li, Fangyu; Zhang, Feng; Chuang, Ru-Jye; Mathur, Mallika; Pomeroy, Mike; Noyola, Jacqueline; Markham, Christine M.; Sharma, Shreela V.
Introduction: Teaching is a stressful occupation due to high-stake job demands and limited resources, which were exacerbated during the initial phase of the COVID-19 pandemic. Our study assessed the prevalence of perceived stress and explored its predictors among elementary school teachers employed at schools serving predominantly low-income populations in five cities in the United States. Method: Our study analyzed the data among selected schools that were collected through the Brighter Bites teacher survey which comprised items measuring sociodemographic characteristics, perceived stress, perceived general health, food insecurity, and concerns regarding social determinants of health needs. The predictors of perceived stress were examined using generalized linear mixed models (GLMMs) with schools as the random variable. Findings: A total of 685 teachers were included in the analysis (84.9% female, 38.1% Hispanic, 57.6% <5 years of teaching experience). Most (85.4%) of the teachers stated they were stressed "sometimes"/"often." Results from adjusted GLMM showed that teachers who were food insecure (adjusted odds ratio [AOR]: 2.33, confidence interval [CI]: [1.63, 3.35]), those who had concerns regarding financial stability (2.68 [1.91, 3.75]), food availability (1.69 [1.15, 2.48]), food affordability (2.27 [1.57, 3.28]), availability/affordability of housing (2.21 [1.33, 3.67]), access to childcare (1.76 [1.06, 2.92]), and access to a clinic/doctor (1.60 [1.10, 2.33]) were at significantly greater odds of reporting perceived stress. Conclusion/Application for Practice: Our study demonstrates the heightened impact of COVID-19 on the mental well-being of teachers across a wide range of social needs. Stress management and additional social service programs are suggested to support teachers to mitigate pandemic impact.